Beauvoir and The Second Sex : Feminism, Race, and the Origins of Existentialism. - Simons, Margaret A. (Rowman & Littlefield Publishers, 2001)
In a compelling chronicle of her search to understand Beauvoir's philosophy in The Second Sex, Margaret A. Simons offers a unique perspective on Beauvoir's wide-ranging contribution to twentieth-century thought. She details the discovery of the origins of Beauvoir's existential philosophy in her hand-written diary from 1927; uncovers evidence of the sexist exclusion of Beauvoir from the philosophical canon; reveals evidence that the African-American writer Richard Wright provided Beauvoir with the theoretical model of oppression that she used in The Second Sex; shows the influence of The Secon.